Ordered mesoporous nickel-cobalt bimetallic catalyst, preparation method and application thereof - HUANG XIN; WANG CHANGZHEN; XIAO FUKUI; SUN NANNAN; ZHAO NING; WANG FENG; WEI WEI (2014)
The invention discloses an ordered mesoporous nickel-cobalt bimetallic catalyst. The ordered mesoporous nickel-cobalt bimetallic catalyst consists of Ni and Co active oxide, additive oxide and aluminium oxide. According to the metal, the molar percent of all metals are as follows: 5-15% of Ni, 0-10% of Co, 0-10% of M and 65-95% of Al, wherein M is one of rare-earth metals or alkaline-earth metals. The ordered mesoporous nickel-cobalt bimetallic catalyst disclosed by the invention has the advantages of high conversion rate, good stability and simple preparation method.